STRUKTUR PENYAJIAN MUSIK IRINGAN TARI RADDAT KOKO DI DESA SEKUDUK KECAMATAN SEJANGKUNG KABUPATEN SAMBAS - Syahdan, Muhammad; Syahrani, Agus; Silaban, Christianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is conducted by the researcher's willingness to find out the form of presentation  of music structure of Raddat Koko dance in Sekuduk Village, Sejangkung District, Sambas Regency. The specific problem is how does the form of presentation of music of Raddat Koko dance in Sekuduk Village,Sejangkung District, Sambas Regency? What are the instruments presented in music accompaniments of Radat Koko dance in Sekuduk Village, Sejangkung District, Sambas Regency?. The method that used in this research is descriptive-explorative in the form of Qualitative. The data that used are from the observation result with the informants and figures who understand about the Raddat Koko dance in Sekuduk Village,Sejangkung District, Sambas Regency. The results of the research are: 1. The presentation structure of the music of Raddat Koko dance in Sekuduk Village,Sejangkung District, Sambas Regency included all the musician plays in the Raddat Koko art, the stage that used, the wardrobe and make up that used, sound system, lighting concept, composition and form of presentation structure. 2. All the instruments presented in accompaniments of the music of Raddat Koko dance in Sekuduk Village,Sejangkung District, Sambas Regency included what are the music used and how to play it. 3) The implementation design of the research results to the study activities in school.   The suggestions for the readers are the researcher hope it can give knowledge about Raddat Koko art in Sekuduk Village,Sejangkung District, Sambas Regency especially for the form of presentation structure of music accompaniments of Raddat Koko dance in Sekuduk Village,Sejangkung District, Sambas Regency.  Keywords : form of music presentation, Raddat Koko Dance, Sambas Malay